Indoor humidity of dwellings and association with building characteristics, behaviors and health in a northern climate. (July 2021) - Psomas, Theofanis; Teli, Despoina; Langer, Sarka; Wahlgren, Paula; Wargocki, Pawel
Abstract: Data from a nationwide survey on the status of the Swedish residential building stock and indoor air quality was placed in the public domain by the National Board of Housing, Building and Planning of Sweden. The current research investigates the indoor humidity conditions in Swedish residential buildings, single-family houses and apartments, assessing the measurements from the extensive BETSI-survey against adjusted relative humidity levels based on existing norms and Standards. The aim of this study is to investigate associations and correlations between relative humidity levels and multiple building and system characteristics, occupancy patterns and behaviors and health symptoms-complaints. The analysis uses 13 categorical and 9 continuous variables-parameters of the examined dwellings. Analysis shows that low indoor relative humidity is a realistic issue in Swedish dwellings during the heating season. The issue is more prevalent in apartments than single-family houses. In addition, low indoor relative humidity seems to be more extensive in dwellings with higher indoor temperature, smaller volume, higher ventilation rate and frequent airing practices, lower number of occupants, constructed mainly after 1985, in city suburbs and in the northern parts of the country. The developed multinomial logistic regression model may predict very accurately the relative humidity level of the Swedish dwellings, during heating season. This analysis offers additional evidence to the scientific literature for possible correlation of low relative humidity with specific health symptoms, complaints and disturbances. Highlights: Low relative humidity is a realistic issue in Swedish dwellings, mainly apartments. The issue is more extensive in dwellings with higher indoor temperatures. Moisture supply values are suggested for this climate and dwellings. Possible correlation of low relative humidity with specific health symptoms. Method may be used widely also in epidemiological and health related campaigns.